Recent climatic, cryospheric, and hydrological changes over the interior of western Canada: a review and synthesis - C. M. DeBeer; H. S. Wheater; S. K. Carey; K. P. Chun (Hydrology and Earth System Sciences, 2016)
It is well established that the Earth's climate system has warmed significantly over the past several decades, and in association there have been widespread changes in various other Earth system components. This has been especially prevalent in the cold regions of the northern mid- to high latitudes. Examples of these changes can be found within the western and northern interior of Canada, a region that exemplifies the scientific and societal issues faced in many other similar parts of the world, and where impacts have global-scale consequences. This region has been the geographic focus of a large amount of previous research on changing climatic, cryospheric, and hydrological regimes in recent decades, while current initiatives such as the Changing Cold Regions Network (CCRN) introduced in this review seek to further develop the understanding and diagnosis of this change and hence improve the capacity to predict future change. This paper provides a comprehensive review of the observed changes in various Earth system components and a concise and up-to-date regional picture of some of the temporal trends over the interior of western Canada since the mid- or late 20th century. The focus is on air temperature, precipitation, seasonal snow cover, mountain glaciers, permafrost, freshwater ice cover, and river discharge. Important long-term observational networks and data sets are described, and qualitative linkages among the changing components are highlighted. Increases in air temperature are the most notable changes within the domain, rising on average 2 °C throughout the western interior since 1950. This increase in air temperature is associated with hydrologically important changes to precipitation regimes and unambiguous declines in snow cover depth, persistence, and spatial extent. Consequences of warming air temperatures have caused mountain glaciers to recede at all latitudes, permafrost to thaw at its southern limit, and active layers over permafrost to thicken. Despite these changes, integrated effects on ...